38.1k views
4 votes
A father racing his son has 1/4 the kinetic energy of the son, who has 1/3 the mass of the father. The father speeds up by 1.2 m/s and then has the same kinetic energy as the son. What are the original speeds of (a) the father and (b) the son?

User Binithb
by
6.3k points

1 Answer

3 votes

Answer:

Step-by-step explanation:

KE_s: Kinetic Energy Son

KE_f: Kinetic Energy Father.

Relationship

KE_f: = (1/4) KE_s

m_s: = (1/3) m_f

v_f: = velocity of father

v_s: = velocity of the son

Relationship

1/2 mf (v_f + 1.2)^2 = 1/2 m_s (v_s)^2 Multiply both sides by 2.

mf (v_f + 1.2)^2 = m_s * (v_s)^2 Substitute for the mass of the m_s

mf (v_f + 1.2)^2 = (m_f/3) * (v_s)^2 Divide both sides by father's mass

(v_f + 1.2)^2 = 1/3 * (v_s)^2 multiply both sides by 3

3*(v_f + 1.2)^2 = (v_s) ^2 Take the square root both sides

√3 * (v_f + 1.2) = v_s

Note

  • You should work your way through all the cancellations to find the last equation shown about
  • We have another step to go. We have to use the first relationship to get the final answer.

KE_f = (1/4) KE_s Multiply by 4

4* KE_f = KE_s Substitute (again)

4*(1/2) m_f (v_f + 1.2)^2 = 1/2* (1/3)m_f *v_s^2 Divide by m_f

2* (v_f + 1.2)^2 = 1/6 * (v_s)^2 multiply by 6

12*(vf + 1.2)^2 = (v_s)^2 Take the square root

2*√(3* (v_f + 1.2)^2) = √(v_s^2)

2*√3 * (vf + 1.2) = v_s

Use the second relationship to substitute for v_s so you can solve for v_f

2*√3 * ( v_f + 1.2) = √3 * (v_f + 1.2) Divide by sqrt(3)

2(v_f + 1.2) = vf + 1.2

Edit

2vf + 2.4 = vf + 1.2

2vf - vf + 2.4 = 1.2

vf = 1.2 - 2.4

vf = - 1.2

This answer is not possible, but 2 of us are getting the same answer. The other person is someone whose math I would never question. She rarely makes an error. And I do mean rarely. Could you check to see that you have copied this correctly?

User Maskacovnik
by
6.1k points